2022
DOI: 10.21037/tlcr-22-467
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of plasma exosomes in patients with non-small cell lung cancer

Abstract: Background: Currently, the prognosis of patients with non-small cell lung cancer (NSCLC) remains unsatisfactory. This current study evaluated the relationship between histology of NSCLC and protein expression of exosomes in the plasma from NSCLC patients, and furthermore investigate the impact of the exosome profile on the tumor, node, metastasis (TNM) classification.Methods: Plasma samples were collected from 26 NSCLC patients before surgery. The exosomes were extracted from the plasma and liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…It has thus been identified as a marker for hepatitis C diagnosis . A higher expression of CD151, CD171, and tetraspanin 8 (TSPAN8) is reported in blood serum exosomes collected from lung cancer patients . These findings suggest exosomal proteins are appropriate biomarkers for cancer diagnosis.…”
Section: Applications Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has thus been identified as a marker for hepatitis C diagnosis . A higher expression of CD151, CD171, and tetraspanin 8 (TSPAN8) is reported in blood serum exosomes collected from lung cancer patients . These findings suggest exosomal proteins are appropriate biomarkers for cancer diagnosis.…”
Section: Applications Of Exosomesmentioning
confidence: 99%
“…323 A higher expression of CD151, CD171, and tetraspanin 8 (TSPAN8) is reported in blood serum exosomes collected from lung cancer patients. 324 These findings suggest exosomal proteins are appropriate biomarkers for cancer diagnosis. Other members of the tetraspanin family such as CD91, CD82, CD147, CD9, and TSPAN8 have also been explored as cancer biomarkers.…”
Section: Proteins Examplesmentioning
confidence: 99%
“…In addition, the MASP-2 gene is also highly associated with lung and endometrial cancer 37 , 38 . MASP-2 expression was higher in patients with lung adenocarcinoma than in people with lung squamous cell carcinoma 39 .…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have indicated that MASP2 gene mutations and changes in the serum MASP2 content are correlated with the prognosis of patients with lung, colorectal, liver, and esophageal cancer. [ 60 , 61 ] C1NH regulates the activation of the C1 complex, which is pivotal in regulating important physiological pathways, including complement activation, venous thrombosis, and kinin generation. Additionally, accumulating evidence indicates the presence of complement components and some regulatory molecules in most carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%